Zishen Yutai pill ameliorates ovarian reserve by mediating PI3K-Akt pathway and apoptosis level in ovary - Jianzhao Chen; Nannan Wang; Zilun Peng; Xiufei Pang; Na Ning; Qingyun Du; Qiuping Guo; Qiuling Huang (Journal of Ovarian Research)
Abstract Zishen Yutai Pill (ZYP) is a widely used Chinese patent medicine in the clinical treatment of diminished ovarian reserve (DOR) induced infertility in China. However, the pharmacological actions and underlying mechanisms of ZYP in treating DOR remain poorly understood. This study aimed to evaluate the therapeutic effects of ZYP on DOR and elucidate its potential mechanisms. Two models including tripterygium glycosides (TGs)-induced DOR rat model and pZP3-induced DOR mouse model were selected to assess the effectiveness of ZYP in treating DOR. The intervention lasted for 4 weeks in both models. ZYP administration significantly increased the primordial follicles and the serum levels of AMH both in DOR rat and mouse model. Further, ZYP regulated the apoptosis pathway and apoptosis-related molecules including PI3K-Akt signaling pathway, Bcl6 and Abtb2 in ovary of DOR rat. The ovarian apoptosis level was significantly downregulated in a dose-depended manner in ZYP groups. Thus, we demonstrate that ZYP improved the ovarian reserve in DOR models. The mechanisms of ZYP on DOR may be mediated through decreasing the apoptosis level by the regulation of PI3K-Akt signaling pathway and apoptosis molecules (Bcl6, Abtb2) in ovary.